The survey of vaccination hesitancy among the residents in Jinan - Dabing Wang; Shiyu Chen; Gaoyu Cui; Dequan Wang; Hong Liu; Lihui Zhao; Xiang Wang; Yuewei Chen (PLoS ONE, 2025)
Introduction Vaccination is an important way to prevent disease, but vaccine hesitancy will impact vaccine coverage and indirectly affect health. This study aims to survey the status of vaccine hesitancy among adults in Jinan. Methods A cross-sectional study was conducted using the vaccine hesitancy scale among the parents of children and teenagers at hospitals in Jinan, China. We described the attitude of the parents to the vaccination through the dimensions of confidence (items: L1-L7) and the risk (items:L8-L10).The participants will be regarded as lacking confidence if the score is over 21 among the items (L1-L7), and participants will consider the vaccination to be a “Risk” if the score is over 9 among the items (L8-L10). Using the chi-square test to analyse the differences of attitude between different participants. Results 202 individuals were enrolled, and most respondents (88.70%) agreed that vaccines are important for their child’s health. 33.50% agreed and strongly agreed that new vaccines carried more risks than older vaccines. The average score for the lack of confidence in the vaccination was 11±0.25. The average score for risk for vaccination was 9.92±0.04. Participants aged below 30 years, females, those with lower education, and those without medical workers in the family were more concerned about the risks of vaccines. Conclusions Participants were confident about the vaccination. But they were also concerned about the risks of vaccines. A lack of vaccine knowledge may led the participants to have hesitancy about vaccinations.